2017
DOI: 10.1111/afe.12235
|View full text |Cite
|
Sign up to set email alerts
|

Response of Drosophila suzukii (Diptera: Drosophilidae) to extreme heat and dryness

Abstract: 1 Drosophila suzukii Matsumura (Diptera) is a polyphagous herbivore native to East Asia that develops in cultivated and wild fruits. In 2011, it appeared in Germany. In 2012, economic damage was recorded and, in 2014, the harvest of stone and soft fruits was lost in some regions. By contrast, during 2015, populations remained lower. Record temperatures and dryness might have impeded population growth during that year. 2 To test this hypothesis, flies were exposed to a 4-day simulation. We evaluated the effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 45 publications
1
15
0
Order By: Relevance
“…The decline in trap captures when tmax > 30 °C in late spring was noted previously [22,30]. Further, it was already suggested that in lab assays, temperatures above 30 °C reduce reproduction or even inhibit it [52,53]. Although our weather data were of quite high resolution (1 × 1 km 2 ), it would be impossible to simulate the authentic field conditions that could vary in much smaller units that provide suitable shelters for D. suzukii .…”
Section: Discussionmentioning
confidence: 56%
“…The decline in trap captures when tmax > 30 °C in late spring was noted previously [22,30]. Further, it was already suggested that in lab assays, temperatures above 30 °C reduce reproduction or even inhibit it [52,53]. Although our weather data were of quite high resolution (1 × 1 km 2 ), it would be impossible to simulate the authentic field conditions that could vary in much smaller units that provide suitable shelters for D. suzukii .…”
Section: Discussionmentioning
confidence: 56%
“…1). Because D. suzukii has a limited tolerance for high temperatures (Tochen et al 2014) and extreme dryness (Eben et al 2018), these observations could explain why we saw peaks of movement into crop fields during the evening hours and high levels of activity at monitoring traps during the morning and evening hours.…”
Section: Discussionmentioning
confidence: 89%
“…On the whole, SWD can survive in thermal conditions ranging from 5 to 30 • C, with the optimum temperature for development and reproduction around 25-28 • C [7,13]. Accordingly, in the Mediterranean area its activity is highest in spring and autumn, with a significant reduction of the populations during hot and dry summers [14].…”
Section: Introductionmentioning
confidence: 99%